Effect of the gate geometry and the injection speed on the flow behaviors of a semi-solid A356 Al alloy - Lee, JC; Seok, HK; Lee, HI (KOREAN INST METALS MATERIALS, 2003)
The effects of the viscosity, gate speed, and gate geometry on the flow behaviors of Al alloys in molten and semi-solid states were studied by direct observations of the flow patterns during die filling. Two different fluids, thixotropic fluid (semi-solid Al alloy) and Newtonian fluid (molten Al alloy), were chosen as the model fluids for monitoring the differences in flow patterns during die filling. High-speed photography was employed to record the real time flow patterns. Qualitative assessments on the critical gate speed were made based on the experimental results. The experimental results were also compared with results predicted based on the Reynolds number. Although the critical gate speed varies depending on the gate geometry, it is less than similar to2.5 m/sec in semi-solid forming, while it ranges from 0.30similar to0.5 m/sec in squeeze casting.